mCrash: a framework for the evaluation of mobile devices trustworthiness properties - Ribeiro, José Carlos Bregieiro (2009)
A rationale and framework for the evaluation of mobile devices’ robustness and trustworthiness properties using a Windows Mobile 5.0 testbed is presented. The methodology followed includes employing software faultinjection techniques at the operating system’s interface level and customising tests to the behaviour of the software.